Studies on essential oils of Alpinia conchigera Griff. from Malaysia - H, Anita,; A.M, Mustafa,; H, Ibrahim, (Malaysian Journal of Science, 2000)
The essential oils of the leaves and rhizomes of Alpinia conchigera were analyzed by GC-MS methods and more than 40 components were detected in the rhizome oil, in which bicycle 4,11,11-trimethyl-8-methylene-undec-4-ene, is the major component. A total of 17 components were found in the leaf oil of which Î²-bisabolene is the major component.